Correlation between porous structure analysis, mechanical efficiency and gamma-ray attenuation power for hydrothermally treated slag-glass waste-based geopolymer. (December 2022) - Mohsen, Alaa; Kohail, Mohamed; Abadel, Aref A.; Alharbi, Yousef R.; Nehdi, Moncef L.; Ramadan, M.
Abstract: The main objective of this work is to compare conventional Portland cement pastes (OPC) and alkali-activated geopolymer pastes in terms of compressive strength, phase composition, micro-porosity, and attenuation ability against harmful gamma irradiation. OPC pastes were cured at 20 °C in tap water for up to 28 days, while geopolymer pastes were prepared by recycling two different industrial byproducts. Equal masses of slag (GGBFS) and recycled glass powder (RGP) were activated by two concentrations of NaOH (5% and 10% mass of total binders). The obtained geopolymer pastes were treated in different manners; some pastes were treated in high humidity at 20 °C and 80 °C for 28 days, while other pastes were cured in an autoclave for different time intervals (2, 4, 8 and 12 hrs) and different steam pressures (4, 6 and 8 bar). A Gamma attenuation capacity test was performed to determine the linear attenuation coefficient (µ) for some selected hardened pastes. Two sources of gamma-ray were used ( 137 Cs/661.6Kev & 60 Co/1332.5Kev). To correlate mechanical performance and attenuation behavior, the N2 -adsorption/desorption technique was conducted to analyze the micro-porosity. The results indicated GGBFS-RGP geopolymer pastes activated by 5 wt% NaOH and thermally hydrated at 4bars for 8hrs possessed the highest compressive strength (86 MPa), highest attenuation ability (µ = 0.156 and 0.126 cm −1 ), highest BET "Brunauer-Emmett-Teller model" surface area (10048 cm 2 /g) and minimum BJH "Barrett-Joyner-Halenda model"-average pore diameter (23.6 nm) as compared with OPC pastes and other all geopolymer pastes. After the autoclaving process, calcium-silicate-hydrate (C-S-Hs), calcium-alumino-silicate-hydrate (C-A-S-Hs), calcium-alumino-hydrate (C-A-Hs), sodium-alumino-silicate-hydrate (N-A-S-Hs) and hexagonal zeolite phase has been achieved via X-ray diffraction analysis (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and scanning electron microscope (SEM/EDX).